Racismo e violência nos contos de Conceição Evaristo - Silva, Agilson da (2024)
This work offers a crucial analysis of contemporary society, focusing on racial prejudice and violence faced by poor black women. By highlighting these aspects, it brings to light a reality that is often neglected by academia and society in general. The gradual, everyday violence against these women is thoroughly explored in the short stories examined, providing important insights into the experience of these marginalized communities. The study seeks to spark reflection on the need for resistance and not letting the struggle and experience of black society, especially women, fall into oblivion. By addressing these issues, the work contributes to a deeper understanding of the social dynamics and injustices faced by black people, in addition to offering support for the formulation of more inclusive and equitable policies and practices. Our objective was to analyze the elements of racism and violence present in Conceição Evaristo’s short stories. This analysis not only highlights the importance of literature as a tool for reflection and awareness, but also highlights the fundamental role of schools in training individuals and disseminating knowledge. By exploring the way in which racism and violence are addressed in Evaristo's work, we seek to show the need to promote cultural resistance and encourage the pleasure of reading in different contexts, especially in the family environment. Furthermore, she highlights the importance of public policies that aim to build a more egalitarian society, addressing issues such as education, culture and social justice. Furthermore, by emphasizing the role of the family in cultural resistance and promoting the pleasure of reading, the study makes explicit the importance of family spaces in the formation of people and the transmission of values ​​and knowledge. Based on Evaristo's stories, we seek to stimulate the development of discourses that promote public policies aimed at building a more egalitarian and fair society. This multidisciplinary and engaged approach highlights the need for concrete actions to combat racism and violence, promoting awareness and encouraging the construction of policies that promote equality and respect for diversity.